Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
x-2x = -3 and x = 3
Step-by-step explanation:
Given the expression
y=x+5.... 1
y-2x=2.... 2
Substituting the first equation into the second we will have;
From 2;
y -2x = 2
x+5-2x = 2
x-2x +5 = 2
x-2x = 2-5
x-2x = -3
-x =-3
x =3
Hence the required equation is x-2x = -3 and x = 3
Answer:
(x + 5) – 2x = 2
Step-by-step explanation:
Edge 2021
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.